Additions to historic buildings: between parasite and prosthetic architecture. Issue 1 (2nd January 2023) - Letzter, Jonathan
ABSTRACT: Addition to historic buildings is an act of planning which integrates the preservation of architectural testimonies while at the same time enabling local development. Building additions are planned and designed under restrictions and regulations and are developed and supervised mainly by global organizations. Additions may be considered a compromise between expanding historic buildings and accentuating the historic buildings' important values. The discussion on the ontological perspective of conservation aspects is directly related to additions. According to conservation discourse, designs of additions are derived after scrutinizing and evaluating the historic building. Therefore, the addition should be visualized differently from both past and present architectural representations. A method to appraise historic buildings' additions is needed to evaluate and justify them. The historic building and its addition are combined as separate entities, and therefore a new term has been proposed to describe this symbiosis: A Combined But-Not Unified Entity (CBNUE). In this article, I propose adding another layer of examination of the CBNUE reciprocity through parasitic and prosthetic architecture theories. This examination challenges the design of additions and offers an alternative view of additions that can be considered appropriate according to international guidelines. Thus, the addition can be considered appropriate within the context of an image of a parasite or a prosthesis.